The relationship between physical fitness and cognitive ability instudents - Hanipah, Ipah; Bastian, Risa Herdiyana (Jurnal Ilmu Keolahragaan, 2023)
Fitness is the ability and capacity This study aims to determine the relationship between physical fitness and cognitive abilities of Grade VIII A students at SMP Negeri 8 Kota Cirebon. The background of this study is based on the low level of student fitness and the absence of similar studies at the school. The research method used was quantitative descriptive with a survey approach and instruments in the form of the Indonesian Physical Fitness Test (TKJI) and report card scores for physical education as indicators of cognitive ability. The research sample consisted of 27 students selected through purposive sampling. The results showed that most students were in the ‘moderate’ physical fitness category and all physical education report card scores were in the ‘good’ category. The normality test showed that the data was normally distributed, but the product moment correlation test produced a significance value of 0.830 (> 0.05), which means that there was no significant relationship between physical fitness and students' cognitive abilities. Thus, it can be concluded that physical fitness is not a factor directly related to students' cognitive abilities in the context of this study.